Impact of cashless payments on the welfare of informal workers in Indonesia: A qualitative study from Yogyakarta - Rahma Yesi; Nia Sunatun Saniyah; Irham Dani; Muhammad Ikhsan; Silverius Djuni Prihatin (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Digital transformation in the financial sector has accelerated the adoption of cashless payments, including among informal workers. However, this group is often marginalized due to limited access to technology and low digital literacy. This study aims to analyze the impact of cashless payments on the welfare of informal workers, particularly in economic, psychological, and behavioral aspects. Using a qualitative approach, data were collected through semi-structured interviews and non-participant observations with 15 informal workers in Srowolan Village, Pakem District, Yogyakarta. Content analysis was used to identify key themes. The findings show improvements in transaction efficiency, a heightened sense of security, and better financial management. Some respondents also reported increased income and greater confidence in managing finances. Nonetheless, challenges persist, including limited access to digital devices, low digital literacy, and the dominance of cash-based habits. This study contributes to the discourse on digital inclusion and highlights the importance of understanding marginalized groups' experiences in adopting technology. The findings are relevant for developing inclusive digital economy policies.   Transformasi digital pada sektor keuangan telah mendorong penggunaan sistem pembayaran non-tunai (cashless), termasuk di kalangan pekerja informal. Namun, kelompok ini sering terpinggirkan karena keterbatasan akses teknologi dan rendahnya literasi digital. Penelitian ini bertujuan untuk menganalisis dampak penggunaan sistem pembayaran non-tunai terhadap kesejahteraan pekerja informal, khususnya dari aspek ekonomi, psikologis, dan perubahan perilaku transaksi. Pendekatan kualitatif digunakan melalui wawancara semi-terstruktur dan observasi non-partisipatif terhadap 15 pekerja informal di Desa Srowolan, Kecamatan Pakem, Yogyakarta. Analisis konten digunakan untuk menemukan tema-tema utama. Hasil penelitian menunjukkan adanya peningkatan efisiensi transaksi, rasa aman, serta kemampuan pengelolaan keuangan. Beberapa responden juga mengalami peningkatan pendapatan dan kepercayaan diri dalam mengatur keuangan. Namun, hambatan seperti keterbatasan perangkat digital, rendahnya literasi, dan kuatnya budaya transaksi tunai masih menjadi tantangan. Penelitian ini memperkaya kajian tentang inklusi digital dan menegaskan pentingnya memahami pengalaman kelompok marginal dalam proses adopsi teknologi. Temuan ini relevan sebagai dasar penyusunan kebijakan ekonomi digital yang inklusif.